Pagdududa: An Initial Inquiry into Filipinos’ Experience of Doubting - Salvador, Divine Love A. (Philippine Social Sciences Review; Volume 63, No. 1, Jan-June 2011, Ed. Eric Manalastas, 2011)
A qualitative inquiry was conducted to gain an initial understanding of Filipinos’ experience of doubting and to arrive at a working definition of duda and an interim conceptual framework for studying pagdududa further. Using non-structured, in-depth interviews, six participants, 3 men and 3 women, were asked to talk about a “karanasan ng pagdududa” (experience of doubting). Participant narratives revealed thematic lines along which further investigation and inquiry can be made: the interconnected elements of the pagdududa story and juxtaposition of context and language of description. From these came a working definition of duda as a psychological condition involving uncertainty, a transitional condition that temporarily stops a person and situates him or her in between two seemingly incompatible states. Recommendations were made for studying duda further and for elucidating the duda-wellbeing link using an interim conceptual framework that views pagdududa as a basic, meaningful, experience that can be harnessed to help people achieve gains in wellbeing.